Incidence of human T-lymphotropic virus 1 infection in adolescent and adult blood donors in Japan: a nationwide retrospective cohort analysis. Issue 11 (November 2016) - Satake, Masahiro; Iwanaga, Masako; Sagara, Yasuko; Watanabe, Toshiki; Okuma, Kazu; Hamaguchi, Isao
Summary: Background: Human T-lymphotropic virus 1 (HTLV-1) infection has an especially high prevalence in Japan. Transmission has been confirmed in infancy through breastfeeding; however, little is known about the epidemiological aspects of new HTLV-1 infections later in life. We aimed to estimate the nationwide annual number of new HTLV-1 infections among adolescents and adults in Japan. Methods: In this retrospective cohort analysis, we assessed new HTLV-1 infections of repeat blood donors aged 16–69 years between Jan 1, 2005, and Dec 31, 2006, in the Japanese Red Cross Blood Centres database. We used results of antibody tests done in repeat blood samples collected until Dec 31, 2011, to assess the number who seroconverted to HTLV-1. We calculated the incidence density by dividing the number of seroconverters by the number of person-years of follow-up, and then extrapolated densities to regional populations to estimate the annual number of new HTLV-1 infections. Findings: We included 3 375 821 HTLV-1-seronegative blood donors (2 100 915 men and 1 274 906 women). Within a median follow-up of 4·5 years (IQR 2·3–5·8), 532 people (204 men and 328 women) had seroconverted. The incidence density was significantly higher in women (6·88 per 100 000 person-years; 95% CI 6·17–7·66) than in men (2·29 per 100 000 person-years; 95% CI 1·99–2·62; p<0·0001). The estimated annual number of new HTLV-1 infections was 4190 (95% CI 4064–4318) with 975 (914–1038) infections in men and 3215 (3104–3328) in women. Interpretation: New HTLV-1 infections in adolescents and adults are an important public health concern in Japan and preventive strategies are needed to reduce new transmission. Funding: Ministry of Health, Labour, and Welfare of Japan; Japan Agency for Medical Research and Development.